Time-Zero Biopsies in Deceased-Donor Kidney Transplantation: Predictive Value of Histological Findings on Long-Term Graft Function - Beirão, Bárbara (2025)
Background:  Time-zero biopsies (TzB) provide insights into donor-derived lesions, but their predictive value for long-term outcomes remains uncertain. We aimed to identify clinical and histological factors from TzB of deceased donors influencing glomerular filtration rate (GFR) at 3- and 5-year post-transplantation. Methods:  We retrospectively analyzed TzB performed from January 2015 to August 2019. Nineteen biopsies were excluded due to recipient death before 3 years. We examined donor and recipient-related characteristics and histological findings categorized using the Banff scoring system. Results:  Among 147 biopsies, 61.9% of donors were male, with a mean age of 51.8 ± 13.5 years, and 27.2% met expanded criteria. Histologic analysis revealed 44.2% had alterations in the Banff chronic scoring system: 29.1% in vascular fibrous intimal thickening (Cv), 26.6% in arteriolar hyalinosis (Ah), and 8.3% in interstitial fibrosis (Ci)/tubular atrophy (Ct). Mean GFR was 54.8 ± 21.2 and 52.3 ± 23.0 mL/min/1.73 m2 at 3 and 5 years, respectively. At 3 years, Ah > 0, Ci/Ct > 0, Cv > 0, Banff chronic sum score > 0, glomerulosclerosis (GE), donor age > 50 years, expanded criteria donors, and rejection episodes were significantly associated with lower GFR. With the exception of Ci/Ct, all other parameters were also significantly associated with lower GFR at 5 years. Linear regression indicated donor age [β (95%CI) = -0.257 (-0.783, -0.021); p = 0.039] and arteriolar hyalinosis [β (95%CI) = -0.207 (-16.767, -0.448); p = 0.039]; p = 0.039) as predictors of GFR at 3 years, with donor age maintaining predictive value at 5 years [β (95%CI) = -0.276 (-0.776, -0.137); p = 0.006]. A tendency towards predictive value for GFR at 5 years was noted for GE [β (95%CI) = -0.198 (120.0, 1.038); p = 0.054]. Conclusion:  TzB provide valuable prognostic information for long-term graft function with histological findings (particularly arteriolar hyalinosis and GE) and donor age serving as significant predictors of GFR at 3 and 5 years post-transplantation. These findings suggest TzB can be useful for risk stratification and personalized management of KT recipients.